2019
DOI: 10.1093/nar/gky1314
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of mutant p53 DNA binding domains reveal a novel druggable pocket

Abstract: The DNA binding domain (DBD) of the tumor suppressor p53 is the site of several oncogenic mutations. A subset of these mutations lowers the unfolding temperature of the DBD. Unfolding leads to the exposure of a hydrophobic β-strand and nucleates aggregation which results in pathologies through loss of function and dominant negative/gain of function effects. Inspired by the hypothesis that structural changes that are associated with events initiating unfolding in DBD are likely to present opportunities for inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 110 publications
2
43
0
1
Order By: Relevance
“…Recent simulations suggest that a subset of mutations could lead to the formation of a druggable binding pocket, potentially opening therapeutic options to restore p53 function [92]. TP53 mutant patients had significantly worse OS in the patient subgroups treated only with endocrine therapy, or no systemic treatment at all ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Recent simulations suggest that a subset of mutations could lead to the formation of a druggable binding pocket, potentially opening therapeutic options to restore p53 function [92]. TP53 mutant patients had significantly worse OS in the patient subgroups treated only with endocrine therapy, or no systemic treatment at all ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Using this methodology we arrived at a final number of 24 pairs Figure 1a) and recessed conformations [46][47][48] Since the tICs are ordered in terms of slowest to fastest motions, the correspondence of L6 anchor features with the first of the components indicates that transitions involving loop L6 are slower than those for loop L1. To further check the importance of these loops in the relevant motions of the protein, we performed additional tICA analysis specifically incorporating other motifs known to play significant roles in p53 function: helices H1 and H2 and loops L2 and L3, which together with L1 make up the DNA interaction surface, and loop S6/7, recently identified as a flexible region in p53 mutants 52 (Figure 1a).…”
Section: L6 Is the Slowest Loop In P53 Dbd Dynamicsmentioning
confidence: 99%
“…Combined molecular dynamics (MD)/experimental studies of R175H [42] and Y220C [43,44] DBD found evidence for previously hidden subpockets, the latter of which were useful in the aforementioned affinity optimizations. More recently, MD simulations of WT DBD and the stabilityclass V143A mutant found differences in the turn region between two beta strands (residues 208-213) [45]. The turn adopts an 'open' conformation in V143A that the authors hypothesized could be The affinity of Y220C cavity binders has progressively improved in recent years.…”
Section: Rescuing Stability Class Mutants: Cavity Bindersmentioning
confidence: 99%